Identification of two bvg-repressed surface proteins of Bordetella pertussis. - Stenson, T H (1995)
Bordetella pertussis, the etiological agent of whooping cough, has the ability to modulate its phenotype in response to environmental conditions by using the BvgAS sensory transduction system which is encoded by the vir locus (now known as bvg). The BvgAS system is part of a large family of two-component sensory transduction systems which are common to a number of pathogenic bacteria. Although much is known about the proteins which exist in the B. pertussis virulent (X-mode or phase I) phenotype, relatively little is known about the proteins produced in the avirulent (C-mode or phase III) phenotype. We used sodium dodecyl sulfate-polyacrylamide gel electrophoresis and isoelectric focusing techniques to demonstrate the existence of at least 22 vir-repressed molecules which are increased in the avirulent phenotype. In addition, a series of monoclonal antibodies which are specific for the surface of avirulent B. pertussis were developed. Using immunological and protein techniques, we characterized two of these antigens as surface-exposed proteins. One of these antigens is expressed only in B. pertussis but not in the related species B. parapertussis and B. bronchiseptica. The other antigen is also present in B. parapertussis and B. bronchiseptica but is expressed at lower levels which are not regulated by bvg. The identification and characterization of vir-repressed proteins (and the genes which encode and regulate them) may help elucidate a physiological role for modulation of this obligate human pathogen.